1999
DOI: 10.1103/physrevb.60.5016
|View full text |Cite
|
Sign up to set email alerts
|

Decay dynamics of photoexcited alkali chemisorbates: Real-time investigations in the femtosecond regime

Abstract: The inelastic decay time of photoexcited cesium and sodium adsorbed on different single-crystal surfaces has been investigated by means of time-resolved two-photon photoemission. Especially in the case of cesium, we observe a surprisingly high lifetime. For Cs/Cu͑111͒ we obtain a value of 15Ϯ6 fs. Intra-atomic hybridization, the specific band structure of the substrate, and adsorption site effects may be responsible for this behavior. These different mechanisms are discussed in detail. ͓S0163-1829͑99͒09231-0͔

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
84
0
2

Year Published

2000
2000
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 125 publications
(92 citation statements)
references
References 47 publications
6
84
0
2
Order By: Relevance
“…A theoretical study, together with a comparison of the available experimental data, of the lifetime of electronically excited states in the Na, K, Rb, Cs/Cu(1 1 1) systems has been made by Borisov et al [328]. The theoretical lifetimes of the excited states are found to increase along the sequence Na, K, Rb, Cs in agreement with the experimental results [281][282][283]288]. This evolution along the alkali series is attributed to the alkali polarizabilities.…”
Section: Adsorbate States: Alkali Metalssupporting
confidence: 69%
See 2 more Smart Citations
“…A theoretical study, together with a comparison of the available experimental data, of the lifetime of electronically excited states in the Na, K, Rb, Cs/Cu(1 1 1) systems has been made by Borisov et al [328]. The theoretical lifetimes of the excited states are found to increase along the sequence Na, K, Rb, Cs in agreement with the experimental results [281][282][283]288]. This evolution along the alkali series is attributed to the alkali polarizabilities.…”
Section: Adsorbate States: Alkali Metalssupporting
confidence: 69%
“…1). The inelastic channel gives similar contributions in both cases leading to values of lifetimes that are in reasonable agreement with the experimental values [281][282][283][284]287]. A theoretical study, together with a comparison of the available experimental data, of the lifetime of electronically excited states in the Na, K, Rb, Cs/Cu(1 1 1) systems has been made by Borisov et al [328].…”
Section: Adsorbate States: Alkali Metalssupporting
confidence: 54%
See 1 more Smart Citation
“…], agree in identifying a resonance above the Fermi level as due to the adsorbate electronic state. 36,37,40,60,61 The atomic character of such a feature is confirmed by its coverage-dependent binding energy 35 and by its dispersion-less behavior in k for very low coverages. 36 Due to its symmetry, i.e., its largest intensity for emission normal to the surface, this resonance has been identified as σ (m = 0).…”
Section: Resultsmentioning
confidence: 74%
“…The experiments show that the realistic electronic properties differ substantially from those obtained on jellium, revealing unoccupied and extremely narrow atomic resonances. [35][36][37][38][39][40][41][42][43] Recently, a phenomenological model has shown that for a good description of the electronic properties of the alkali adatom systems is crucial to account for the main characteristics of the electronic properties of the substrate. 44,45 Nevertheless, such a model is also based on the assumption of a complete ionization of the adatom.…”
Section: Introductionmentioning
confidence: 99%